Yohimbine-Induced Circadian Clock Resetting in Mice - Isaacson, Alexandra; Ruff-Berganza, Sophia (My University, 2012)
Mice are nocturnal animals that exhibit predictable activity patterns controlled by their internal (circadian) clock. This study demonstrated that a mouse's circadian clock can be reset to an earlier time through the administration of yohimbine, a selective adrenergic agonist. This study also looks at whether the yohimbine's clock resetting effect is dependent on the time of day at which it is administered.
Color poster with text, graphs, and diagrams.
Keywords: Yohimbine; Circadian rhythms--Effect of drugs on; Posters; Mice--Behavior